Interpretation of Tantri’s Nonverbal Dialogue in Kamila Andini’s Film The Seen And Unseen - Ilfilia, Amanda Tiara; Rustim (Kirana Publisher (KNPub), 2025)
This study analyzes the nonverbal dialogue of the character Tantri in Kamila Andini’s The Seen and Unseen through Roland Barthes’s semiotic framework (denotation, connotation, myth) and Konstantin Stanislavski’s acting system (given circumstances, inner action, physical action). The research focuses on bodily gestures, facial expressions, artistic settings, symbolic properties (such as eggs, children in white shirts, cockfight dance), and ambient soundscapes that signify the transition between the sekala niskala (seen unseen) realms. Primary data include the film itself and key sequences, supported by literature, interviews, and cultural sources on Balinese cosmology. The findings show that the egg serves as a symbolic sequence representing the world and Tantri and Tantra’s twin bond, the cockfight and “chicken dance” metaphorically express the life death tension, children in white shirts represent catur sanak, the unseen siblings who guide Tantra’s departure, physical actions in performance embody genuine emotion without reliance on spoken dialogue. This film situates body language and cultural symbolism as primary narrative instruments for expressing grief and separation.